Laparoscopic nephrectomy versus transperitoneal anterior approach in living donors for renal transplantation - Maciel , Rafael Fabio; Felski , Isadora; Sakaguchi , Hugo; Costa, Thais (Brazilian Journal of Transplantation, 2005)
Objective: The objective of this study is to compare two different surgical approaches for living donor nephrectomy, transperitoneal anterior approach and hand-assisted laparoscopic nephrectomy. Methods: Between January 2001 and October 2003 we performed 63 kidney transplantations with living donors. The transperitoneal anterior approach was used in 36 cases and the hand-assisted laparoscopic nephrectomy in twenty-seven. They were compared in terms of hospital stay, post-operative analgesia and quality of graft. Results: Mean hospital stay was 4,7 days in the transperitoneal anterior approach group and 3,7 days in the hand-assisted laparoscopic group (p<0.005). The dosage of post-operative analgesia was significantly lower in the hand-assisted laparoscopic group (p<0.001). Surgical complications and graft quality were similar. Conclusion: We have concluded that hand-assisted laparoscopic nephrectomy patients had less hospital stay and less pain in the post-operative period, with better cosmetic results and equivalent graft quality compared to transperitoneal anterior approach patients.